Prevalence trends of hypertension and influence factors among children and adolescents aged 7–17 years in China, 2011–2015: A serial cross-sectional study - Yang, Yunjuan; Dai, Jing; Min, Jieqing; Wu, Huamei; Huang, Songquan; Li, Qingsheng; Chai, Jiajia (Frontiers in Public Health, 2022)
Hypertension has rapidly increased in the last decades throughout the world. It is an emerging disease. But limited information is available on secular trends and factors of childhood and adolescents’ hypertension in China. In this study, five-year successive data were derived from the China Health and Nutrition Survey (CHNS) cross-sectional study in 2011 and 2015. We used SBP and/or DBP at least 95th percentile on the basis of age, sex, and height percentiles to define HBP. A total of 2,827 7-17 aged children and adolescents were included. The age-standardized prevalence of hypertension increasing significantly across five years: the standardized hypertension prevalence was increased from 8.08% (2011) to 11.46% (2015) in China (P＜0.01). The mean SBP of boys increased from 101.21mmHg to 102.79mmHg. The mean SBP of girls increased from 98.96mmHg to 100.04mmHg; The mean DBP of boys increased from 61.20mmHg to 67.40mmHg, while the mean DBP of girls increased from 64.34mmHg to 65.76mmHg. The prevalence of hypertension grew continuously in both sexes, but the pace of change for boys were rapider than that for girls. This study confirmed the association between rural (OR=1.394, 95%CI 1.032-1.883), overweight/obesity (OR=2.621, 95%CI 1.506-4.562) and BP levels had highly correlated (P＜0.05). The girl was possible protect factors associated with hypertension (OR=0.788, 95%CI 0.595-1.043). There were no association between weekly physical activity, daily sleep duration and hypertension(P＞0.05). Further deeply analysis of influencing factors and comprehensive interventions should be urgently implemented to combat the hypertension epidemic among children and adolescents in China.